NEUROCRANIUM OF CYNOGLOSSUS AREL (SCHNEIDER), A COMMON INDIAN FLATFISH, WITH SPECIAL REFERENCE TO ASYMMETRY - Das, Mihir; Datta, Naresh C (Indian Journal of Fisheries, 2011)
The asymmetry is prominent in the neurocranium of Cynoglossus arel. The frontals are extremely asymmetrical, curving on the ocular side to accommodate the displaced right eye. The lateral ethmoid of the ocular side possesses a larger aperture for the exit of the olfactory nerve. On the blind side, the aperture for the trigeminal and vagus nerves are relatively large and the lacrymal larger in size.